2006
DOI: 10.1007/s00381-006-0174-8
|View full text |Cite
|
Sign up to set email alerts
|

A novel brainstem tumor model: functional and histopathological characterization

Abstract: The establishment of this animal tumor model will facilitate the testing of new therapeutic paradigms for the treatment of BSTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 25 publications
1
30
0
Order By: Relevance
“…4). 56,57,65,123 Wu et al 122 demonstrated that carboplatin could be locally delivered to neoplastic cells in a rat brainstem tumor model with mini-osmotic pumps, which resulted in a prolongation of survival. Moreover, Lonser et al 71 documented the safety of locally infused Gd-bound albumin via stereotactically implanted cannulas into large areas of the primate midbrain and pons, followed by other reports showing the safety of CED of chemotherapeutic agents, such as gemcitabine and carboplatin, infused into the primate brainstem, although dose-dependent toxicity has been found with carboplatin.…”
Section: New Therapeutic Perspective Strategiesmentioning
confidence: 99%
“…4). 56,57,65,123 Wu et al 122 demonstrated that carboplatin could be locally delivered to neoplastic cells in a rat brainstem tumor model with mini-osmotic pumps, which resulted in a prolongation of survival. Moreover, Lonser et al 71 documented the safety of locally infused Gd-bound albumin via stereotactically implanted cannulas into large areas of the primate midbrain and pons, followed by other reports showing the safety of CED of chemotherapeutic agents, such as gemcitabine and carboplatin, infused into the primate brainstem, although dose-dependent toxicity has been found with carboplatin.…”
Section: New Therapeutic Perspective Strategiesmentioning
confidence: 99%
“…There have been many laboratory studies investigating local delivery into an animal brainstem without tumors. Recently, a rat model of brainstem glioma has been developed [14,30]. Moreover, several feasibility studies were performed with continuous drug infusion into brainstem using carboplatin, BCNU, IL-13-PE, and gemcitabine [5,18,20,24].…”
Section: Introductionmentioning
confidence: 99%
“…We report our initial experience of temozolomide administration into the brainstem by intracerebral microinfusion using the guiding screw technique in the rat brainstem GBM allograft model established at our institution [11,13,14,16,30].…”
Section: Introductionmentioning
confidence: 99%
“…Even if the automated infusion pump is cost prohibitive for some groups, cells can still be injected manually more quickly than stereotactic approaches. Overall, this rapid, accurate and reproducible method can be used to study glioma, medulloblastoma and brain stem tumors 7 . This procedure has been performed on over 500 mice between our two laboratories with deaths due to unexpected anesthetic reactions (<1%).…”
Section: Discussionmentioning
confidence: 99%